Pengaruh Tekanan Stakeholders dan Tanggung Jawab Sosial terhadap Penerapan Akuntansi Lingkungan di Kawasan Industri Makassar - M Wahyuddin Abdullah; Saiful Muchlis; Sri Nirmala Sari (Universitas Islam Negeri Alauddin Makassar, 2015)
This study aims to provide empirical evidence of the influence of the pressure of stakeholders and social responsibility to the implementation of environmental accounting, and the most dominant influence between pressure stakeholders with social responsibilities towards the implementation of environmental accounting. The population of study was company in Makassar Industrial Area (KIMA). Find were the method using purposive sampling and obtained by respondents as many as 70 managers from 11 companies sampled. Hypothesis testing using multiple regression models with independent variables pressure of stakeholders that includes government regulation, public pressure, the pressure of environmental organizations, and corporate social responsibility, and the dependent variable is the implementation of environmental accounting. The results showed that the pressure of stakeholders in the form of government regulation and corporate social responsibility significantly influence the implementation of environmental accounting, while the pressure of stakeholders in the form of public pressure and the pressure of environmental organizations did not significantly influence the implementation of environmental accounting.